Using peer narrative support to promote return to work for cancer survivors: a protocol study of action research - Wenqian Que; Xiaoyun Hu; Tingting Wu; Haiyin Zhang; Yue Shi; Jingyi Zhao; Xiaoqin Su; Benxin Kuai; Yujie Guo (Archives of Public Health)
Abstract Background Chinese cancer survivors are not doing well in returning to work. Peer support, as an external coping resource to help cancer survivors return to work, brings together members of the lay community with similar stressors or problems for mutual support. Peer volunteers have not received systematic training, so inappropriate language in the support process can often cause secondary damage to both the peer and the cancer survivor. High-quality narrative support can help both parties gain positive meaning in communication. Therefore, we draw on narrative-related theoretical techniques to construct a model of peer narrative support to facilitate cancer survivors’ return to work. Methods This study is a participatory action research, including three phases: (i) Construction: Construct a peer narrative support model through literature review, theoretical research, and expert meetings. A peer narrative competence training program and a peer narrative support implementation program are constructed on this basis. (ii) Intervention: Firstly, two rounds of training actions will be carried out for 8 weeks. Second, after the peers have passed the training assessment, cancer survivors will be recruited to carry out two rounds of peer narrative support for six months. The model framework will be revised in conjunction with observation and reflection during the action. (iii) Evaluation: A combination of quantitative and qualitative methods will be used to assess the feasibility and scientific validity of the peer narrative support model and to evaluate the effectiveness of the intervention. The research methods used include theoretical research, literature review, expert meeting method, participatory observation method, interview method, and questionnaire survey method. Discussion China currently has cancer rehabilitation associations in most provinces, cities, and counties, and peer volunteers in these organisations use their personal experience to help other cancer patients. Currently, the content of their help is mostly limited to disease recovery and financial condolences, and there is a lack of scientific training for peer volunteers. This study aims to help patients cope with their suffering and eventually return to work by narrating the stories of role models. The narrative support covers three aspects: focusing on recovery, rebuilding effectiveness, and adjusting planning. In addition, this study relies on the methodology of action research to develop a peer narrative support model, training program, and implementation plan, which are more applicable to the national context of peer support for cancer patients in China. This will provide scientific guidance for the Chinese Cancer Rehabilitation Association to develop peer narrative support and guide cancer survivors back to work. Trial registration This study has been registered at the Chinese Clinical Trial Registry (Registration number ChiCTR2300068403) on Feb 17, 2023. (Retrospectively registered) https://www.chictr.org.cn/bin/project/edit?pid=183766 .